2021
DOI: 10.3390/agriculture11050431
|View full text |Cite
|
Sign up to set email alerts
|

Cherry Tree Crown Extraction from Natural Orchard Images with Complex Backgrounds

Abstract: Highly effective pesticide applications require a continual adjustment of the pesticide spray flow rate that attends to different canopy characterizations. Real-time image processing with rapid target detection and data-processing technologies is vital for precision pesticide application. However, the extant studies do not provide an efficient and reliable method of extracting individual trees with irregular tree-crown shapes and complicated backgrounds. This paper on our study proposes a Mahalanobis distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…To validate the proposed method's crown segmentation performance on fruit trees, this study compared it with the K-means clustering algorithm and GMM (Gaussian mixture model) algorithm, which were unsupervised image segmentation methods that are widely used for fruit crown segmentation [42,44,63]. AOCC, POCC, FOCC, MOCC, and ROCC are combined into a feature matrix M as the segmentation feature of K-means and GMM algorithms.…”
Section: Evaluation Of Image Segmentation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate the proposed method's crown segmentation performance on fruit trees, this study compared it with the K-means clustering algorithm and GMM (Gaussian mixture model) algorithm, which were unsupervised image segmentation methods that are widely used for fruit crown segmentation [42,44,63]. AOCC, POCC, FOCC, MOCC, and ROCC are combined into a feature matrix M as the segmentation feature of K-means and GMM algorithms.…”
Section: Evaluation Of Image Segmentation Methodsmentioning
confidence: 99%
“…The authors compared the proposed method with the results of FCN segmentation and the results showed that that the model can improve the detection rate of canopy by 34.7%. In a word, supervised learning can achieve highprecision segmentation, but it relies on complex feature engineering or large-size labeled data [42]. Yuzhen et al [43] summarized 34 data sets of machine vision in agriculture, among which there are no open datasets for fruit tree segmentation as yet.…”
Section: Materials and Study Areamentioning
confidence: 99%
“…Various studies have focused on image segmentation based on scenes. The current agricultural field segmentation and delineation approaches can be mainly divided into three categories: threshold-based methods [7][8][9], texture analysis technique methods [10][11][12][13], and trainable classification model methods [14][15][16][17]. The development of deep neural networks provided new opportunities for agricultural scene extraction by extracting the target features automatically to save the pre-processing costs, and their architectures are highly adaptive to complex problems [18].…”
Section: Introductionmentioning
confidence: 99%
“…The manual-feature-based image segmentation method can only use limited features such as color information, texture information, and spatial structure of images for image segmentation due to the limited computational performance of the computer. This process is time-consuming and ineffective in more complex cropland segmentation, such as threshold segmentation [ 7 , 8 , 9 ], texture analysis [ 10 , 11 , 12 , 13 ], edge extraction [ 14 , 15 , 16 ], and region-based segmentation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%